2010
DOI: 10.1111/j.1365-2249.2010.04201.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammatory cells, cytokines and matrix metalloproteinases in neutrophil-mediated skin diseases

Abstract: SummaryPyoderma gangrenosum (PG) is a rare, immune-mediated inflammatory skin disease presenting with painful ulcers having undermined edges. Less commonly, bullous and vegetative variants exist. Histology consists of a neutrophil-rich dermal infiltrate. We characterized immunohistochemically the infiltrate in different variants of PG and in another neutrophilic dermatosis as Sweet's syndrome. We studied 21 patients with PG, eight with Sweet's syndrome and 20 controls, evaluating skin immunoreactivity for infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
172
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(191 citation statements)
references
References 28 publications
10
172
0
9
Order By: Relevance
“…Furthermore, the increase of elafin, the neutrophil elastase inhibitor, expressed by injured epidermal keratinocytes, and the intensification of the FAS/FASL system, involved in tissue damage and apoptosis, may also contribute to the formation of ulcers in PG, and impairment of tissue remodeling and wound healing. 10,13,14 IL17 produced by Th17 cells, shown to play an important role in IBD and other skin diseases that involve neutrophil recruitment, like psoriasis and acute generalized exanthematous pustulosis, has also been found to be elevated in skin lesions of PG. 12,[14][15][16] Th17 cells seem to be overrepresented in PG lesions together with a low level of regulatory T cells (Treg) and related cytokines, namely IL10.…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the increase of elafin, the neutrophil elastase inhibitor, expressed by injured epidermal keratinocytes, and the intensification of the FAS/FASL system, involved in tissue damage and apoptosis, may also contribute to the formation of ulcers in PG, and impairment of tissue remodeling and wound healing. 10,13,14 IL17 produced by Th17 cells, shown to play an important role in IBD and other skin diseases that involve neutrophil recruitment, like psoriasis and acute generalized exanthematous pustulosis, has also been found to be elevated in skin lesions of PG. 12,[14][15][16] Th17 cells seem to be overrepresented in PG lesions together with a low level of regulatory T cells (Treg) and related cytokines, namely IL10.…”
Section: Pathophysiologymentioning
confidence: 99%
“…8 In PG and other neutrophilic diseases, elevated skin and/or circulating levels of the pro-inflammatory cytokines (IL1β, IL6, TNF-α, IFN-ϒ, G-CSF) [10][11][12] and, particularly, of the potent PMN attracting chemokines, namely IL8/CXCL8 and CXCL1,2,3, along with skin infiltration by T cells, particularly at the edge of the PG ulcer, suggests an active recruitment of PMN to the skin. 10,13 Also, in both PG and SS skin lesions, there is a high expression of MMPs (MMP-2, MMP-9, MMP-10), a family of Zn2+ endopeptidades that are not only major contributors to the breakdown and reconstitution of the extracellular matrix in wound repair, but also influence the production of neutrophilic chemokines in neutrophilic disorders. Furthermore, the increase of elafin, the neutrophil elastase inhibitor, expressed by injured epidermal keratinocytes, and the intensification of the FAS/FASL system, involved in tissue damage and apoptosis, may also contribute to the formation of ulcers in PG, and impairment of tissue remodeling and wound healing.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we recently demonstrated a marked expression of IL-8 by the cells composing the dermal inflammatory infiltrate in PG, particularly 'l-Iymphocytes and macrophages, with the most intense IL-8 labelling at the wound bed, where there is the predominant neutrophil recruitment and consequent tissue damage (14). In the present study, we found hyperexpression of IL-8 also in APF, but its immunoreactivity was significantly lower than in PG and similar to that seen in Sweet's syndrome.…”
Section: Fig 5 Immunohistochemical Studies Of Matrix Metalloproteinmentioning
confidence: 99%
“…Received January 5, 2011 -Accepted April 14,2011 Amicrobial pustulosis of the folds (APF) is a rare cutaneous disease characterized by relapsing sterile pustules frequently associated with autoimmune disorders. Although APF pathophysiology is still undefined, scattered reports suggest involvement of neutrophils.…”
mentioning
confidence: 99%